DIAGNOSTICS OF NON-RHEUMATIC CARDITIS IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Heart muscle lesions are most often of non-rheumatic etiology, the main causes may be viral infections rather than bacterial ones. Research by N.A. Belokon et al. showed that in children, non-rheumatic carditis (NRC) can be congenital or acquired [1-8].